Glittering Facts of Gold - Shankari, S. (Indian Journal of Finance, 2011)
India is the largest consumer of gold jewellery in the world, accounting for about 20 per cent of global gold consumption. According to a release by the World Gold Council, during the first quarter of 2010 (Jan-Mar), India was ranked as the strongest performing market on the back of increase in consumer demand. The country registered an increase of 698 per cent to 193.5 tonnes. Although, the market is highly dominated by the unorganized players, with increase in consumer income and economic prosperity, the future of organized retail in India is very bright. The pricing factor of gold influences the purchasing behavior of jewels by the people. Hence, the study took up the pricing behavior of gold.